Intrinsically Electron Conductive, Antibacterial, and Anti‐swelling Hydrogels as Implantable Sensors for Bioelectronics. (22nd September 2022) - Xia, Xiangjiao; Liang, Quanduo; Sun, Xiguang; Yu, Dehai; Huang, Xinrui; Mugo, Samuel M.; Chen, Wei; Wang, Dong; Zhang, Qiang
Abstract: New materials and devices for bioelectronics have emerging applications in healthcare monitoring and disease diagnostics. Hydrogel‐based sensors face great challenges in achieving desirable synergistic performances including intrinsical electron conduction, bacterial resistance, anti‐swelling property, and adhesion to tissues. To address current bottlenecks, poly(Cu‐arylacetylide) derived hydrogels are developed for the first time that demonstrates all these above intriguing performances as a result of the special Cu‐arylacetylide backbone. The hydrogels show the capability of recording electrocardiogram (ECG), electromyogram, implantable epicardial ECG, and transmitting neural signals. Furthermore, the Cu (I) in polymer chains can be substituted by other metal ions such as Au (I), which can create numerous new materials with intriguing performances. This study not only creates a new research field of hydrogels but advances design concepts for implantable electrodes to record bio‐electron. Abstract : Poly(Cu‐arylacetylide) derived hydrogels are synthesized to break the current bottleneck of hydrogel‐based materials, which demonstrate a series of intriguing performances such as good electron conductivity, remarkable adhesiveness performance, outstanding swelling resistance, excellent antibacterial property, and good biocompatibility. The hydrogels show reliable capability for bioelectronics.